Penetapan Bahan Organik Tanah Tandus Secara Spektrofotometri & Titrimetri - Raharjo, R (Laboratorium Bio Teknologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
The content of organic matter in barren land and padas has been determined spectrophotometrically and titrimetrically. Soil samples were taken from four locations, each of the two locations of barren land (I and II) and two locations (I 'and II'). The content of soil organic matter at depths of 15, 50 and 90 cm determined spectrophotometrically, is 24.48; 17.29 and 9.07% (Location I), 19.64; 15.92 and 6.24% (Location II). With the titrimetry method on solid soil, the yield obtained is 1.30; 0.94 and 0.76% (Location I '), 0.64; 0.46 and 0.31% (Location II'). It appears, that the deeper the content of organic matter the lower the soil. When compared with barren land, the content in padas is lower.